The Development of Local-Based Learning Activities in an Integrated Learning Unit Entitled “The Legend of Phra Yuen Kantharawichai” for Grade 5 Students - Montree Wongsaphan; Chowwalit Chookhampaeng; Hemmin Thanapatmeemanee; Pornvenus Noomtuam (Journal of Educational Issues, 2024)
The objectives of this study were 1) to develop local-based learning activities in an integrated learning unit entitled “The Legend of Phra Yuen Kantharawichai” for grade 5 students; 2) to compare the student’s academic achievement with a criterion of 80%; 3) to compare the students’ historical process skills with a criterion of 80%; 4) to compare the students’ geographic skills with a criterion of 80%; and 5) to assess the students’ local pride. The participants obtained by cluster random sampling method were 34 students of grade 5/2 students studying in the second semester of the academic year 2021, at Mahasarakham University Demonstration School (Elementary). The instruments were 1) a lesson plan; 2) an academic achievement test; 3) a historical process skills assessment form; 4) a geographic skills assessment form; and 5) a measure of local pride. Analysis of the data was percentage, mean score, standard deviation, and t-test. The results of the study showed that 1) the efficiency of the lesson plan was 93.82/84.12, which met the specified 80/80 criteria; 2) the student’s academic achievement was significantly higher than the establishment at the criterion of 80% at a statistical level of .01; 3) the students’ historical process skills were significantly higher than the establishment at the criterion of 80% at a statistical level of .01; 4) the student’s geographic skills were significantly higher than the establishment at the criterion of 80% at a statistical level of .01; and 5) the students’ overall local pride was at the highest level. It was concluded that local-based learning could develop students to achieve academic achievement, historical process skills, and geographical skills that meet the goal and make students feel local pride for learning in history subjects that integrate geography and local content.